IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER RELIGIUS SISWA DI SMK NEGERI 12 MALANG - Siti Badriyah; Chalimatus Sa'dijah; Ahmad Subekti (VICRATINA, 2019)
Based on the functions and objectives of National Education clearly states that education is a means of forming good character and religious behavior, so as to produce human beings who are noble, have a healthy mind, are creative, independent, and are responsible and obedient citizens. The purpose of this research was to find out how intracurricular, co-curricular, and the curricular learning of Islamic religious education in shaping the religious character of students at Malang State Vocational High School 12. The research approach used by the author is a qualitative approach and a type of case study research. Data sources come from primary and secondary data. Data collection techniques are by participant observation, in-depth interviews, and documentation. Located at SMK Negeri 12 Malang. Techniques in analyzing data include data display (data presentation) that is presenting data from the reduction process in the form of tables, graphics, and the like so that they are easily understood. conclusion drawing or verification, namely drawing conclusions and verification from initial conclusions that are temporary and then reinforced with subsequent evidence.From the results of the study, the conclusions of the intracuricular learning of Islamic religious education class XI TSM 1 were obtained in the form of the application of lecture and question and answer methods, and using a scientific approach. Kokurikuler activities in the form of dhuha prayers, 3S, shaking hands, dhuhur prayer and shar in congregation, berdo'a and tadarus Al - Qur'an, and istighosah together. And extracurricular activities in the form of Islamic organizations namely BDI (Islamic Da'wah Agency) which includes Islamic studies, keputrian studies, and Islamic art.With the intracurricular, kokurikuler, and extracurricular learning models above, students have a higher religious spirit, are responsible for compulsory prayer, and have a tolerant spirit in accordance with national education goals.